Sea Alms Tradition from the Perspective of Network Actor Theory in Coastal Communities of Rowo Village, Kebumen - Mubarok, Kasirul; Mundayat, Arif Aris; Ramdhon, Akhmad (KnE Social Sciences, 2024)
This study analyzes the relationship between the fishing community and the sea which is manifested through the ritual of sea alms. The theory used is Bruno Latour’s ANT theory which has five concepts, namely actors, networks, actants, translations, and intermediaries. The researcher focuses on the concept of network actors, and translations. The research method used is the descriptive qualitative research method. Data were collected through interviews, observation, and documentation. The informants who were interviewed were fishermen, fishermen’s families, traditional leaders (community leaders), and the surrounding community following the sea alms tradition. The results show that the process of the sea alms tradition begins with a procession to the river mouth to bring umborambe (offerings) which are put into julen (miniature joglo houses) containing clothing, goat heads and feet, fruits, and other objects that are considered the favorite of the ruler of the ocean (Nyi Roro Kidul) to be floated to the sea. Bruno Latour’s ANT theory explains that there is a relationship between humans and non-humans that influence each other and form a network in the form of sea alms. This tradition brings together humans and non-humans to remain balanced and mutually influential. Keywords: sea alms-1, actors-2, networks-3 , translation-4